2017
DOI: 10.1038/am.2017.185
|View full text |Cite
|
Sign up to set email alerts
|

Lipid nanoparticle-mediated efficient delivery of CRISPR/Cas9 for tumor therapy

Abstract: The emerging CRISPR/Cas9 system represents a promising platform for genome editing. However, its low transfection efficiency is a major problem hampering the application of the gene-editing potential of CRISPR/Cas9. Herein, by screening a pool of more than 56 kinds of agents, we constructed a novel polyethylene glycol phospholipid-modified cationic lipid nanoparticle (PLNP)-based delivery system that can condense and encapsulate a Cas9/single-guide RNA (sgRNA) plasmid (DNA) to form a core-shell structure (PLNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
123
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(123 citation statements)
references
References 28 publications
0
123
0
Order By: Relevance
“…The lipid formulation was composed of three components: 1,2‐dioleoyl‐3‐trimethylammoniumpropane (DOTAP), dioleoylphosphatidylethanolamine (DOPE), and cholesterol. The nanoparticles were used to deliver Cas9/sgPlk‐1 plasmids for editing Plk1 genes in melanoma tumor‐bearing mice and the results obtained demonstrated that it could decrease the expression of Plk1 proteins and restrain the process of tumor growth (Figure A, B) …”
Section: Non‐viral Vectors Of Crispr‐cas9mentioning
confidence: 99%
See 1 more Smart Citation
“…The lipid formulation was composed of three components: 1,2‐dioleoyl‐3‐trimethylammoniumpropane (DOTAP), dioleoylphosphatidylethanolamine (DOPE), and cholesterol. The nanoparticles were used to deliver Cas9/sgPlk‐1 plasmids for editing Plk1 genes in melanoma tumor‐bearing mice and the results obtained demonstrated that it could decrease the expression of Plk1 proteins and restrain the process of tumor growth (Figure A, B) …”
Section: Non‐viral Vectors Of Crispr‐cas9mentioning
confidence: 99%
“…(B) Western blot analysis of Plk1 protein expression in tumors. Reproduced with permission . (C) Preparation processes for lipid‐encapsulated TAT peptide‐modified AuNPs (LACPs) and (D) schematic illustration of laser‐enhanced knockout of targeted genes by LACP in A375 cells.…”
Section: Non‐viral Vectors Of Crispr‐cas9mentioning
confidence: 99%
“…Much research has been carried out and some progress has been made regarding a prominent disadvantage of the CRISPR/Cas9 gene editing technology, namely off‐target effects . Other studies have focused on efficient delivery of the CRISPR/Cas9 system and associated clinical issues . T‐cells modified by CRISPR/Cas9 have been used to treat cancer by mobilizing the patient's immune system.…”
Section: Challengesmentioning
confidence: 99%
“…In lipid‐based delivery systems, cationic lipids usually encapsulate anionic Cas9 DNA, mRNA, or protein through electrostatic interactions, and this precludes degradation of the CRISPR/Cas9 system and the immunological response of the organism. Recently, our group reported a polyethylene glycol (PEG)‐modified cationic lipid‐based nanoparticle that condenses the protamine/Cas9‐gPlk‐1 plasmid DNA/chondroitin sulfate ternary complex to form a core–shell structure with about 47.4 % transfection efficiency in A375 cells in vitro and 67 % suppression of tumor growth in vivo . Other work has identified lipids from a library of synthetic cationic lipids that effectively deliver the Cas9 protein.…”
Section: Delivery Of Crispr/cas9mentioning
confidence: 99%
“…Recently,o ur group reported ap olyethylene glycol (PEG)-modified cationic lipid-based nanoparticle that condenses the protamine/Cas9-gPlk-1 plasmidD NA/ chondroitin sulfate ternary complex to form ac ore-shell structure with about 47.4 %t ransfection efficiency in A375 cells in vitro and 67 %s uppression of tumor growth in vivo. [33] Other work has identified lipids from al ibrary of synthetic cationic lipids that effectively deliver the Cas9 protein. This screening has shed light on the structure-activity relationship between lipid structure and delivery efficacy.…”
Section: Physical Deliverymentioning
confidence: 99%